A new approach for determination of single component gas hydrate formation kinetics in the absence or presence of kinetic promoters. (1st December 2015) - ZareNezhad, Bahman; Mottahedin, Mona; Varaminian, Farshad
Abstract: The kinetics of single component gas hydrate formation processes at isochoric or isobaric operating conditions with and without using the kinetic additive have been experimentally and theoretically determined. In the proposed kinetic model, the coupled equations of hydrate stability and mass balance are solved such that the conventional equilibrium calculations for expressing the driving force is not necessary. The driving force, occupancy factor, Langmuir constant and free energy change are expressed in terms of gas hydrate former composition in the liquid phase. The introduced kinetic rate constant which is the only adjustable parameter of the proposed model is a weak function of the temperature and a strong function of the surfactant concentration. It is shown that the determined kinetic rate constant is independent of the employed isochoric or isobaric operating modes and is independent of the operating pressure. The overall AAD% and R 2 -value of the calculated gas molar consumptions regarding methane (C1 ), ethane (C2 ) and carbon dioxide (CO2 ) hydrate formation processes at isochoric or isobaric operating conditions with and without using the sodium dodecyl sulfate (SDS) kinetic promoter are about 1.91% and 0.997 respectively suggesting the excellent accuracy of the proposed kinetic model. Highlights: A new approach for prediction of single gas hydrate formation kinetics is presented. A series of experiments for C1, C2 and CO2 hydrate formation with SDS is carried out. The driving force is expressed in terms of gas composition in the liquid phase. The kinetic rate constant is independent of the isochoric or isobaric operating modes. The AAD% and R 2 -value of the predicted results are about 1.91% and 0.997, respectively.